Inhibiting the RNA helicase DDX3X in Burkitt lymphoma induces oxydative stress and impedes tumor progression in xenografts - Beauchemin, Hugues; Dalloul, Zeinab; Piskor, Eva-Maria; Calderon, Virginie; Chatr-aryamontri, Andrew; Bertomeu, Thierry; Möröy, Tarik (Frontiers in Cell and Developmental Biology, 2025)
IntroductionBurkitt Lymphoma (BL), an aggressive B-cell lymphoma driven by MYC translocations, requires intensive chemotherapy treatments which deliver high effectiveness yet increase future risks of developing secondary malignancies. We have previously shown that DDX3X, an RNA helicase frequently mutated in BL, is essential for B cell lymphomagenesis in mice.Methods and resultsTo assess if DDX3X could therefore represent a promising therapeutic target for BL, we tested two DDX3X inhibitors, the well characterized RK-33 and the more potent newly developed C1, in three BL cell lines (CA46, Raji, Daudi). We found that the 3 cell lines exhibited differential sensitivities to the drugs in vitro, with Daudi being the most susceptible and Raji the most resistant. In vivo, RK-33 treatment in a xenograft BL model reduced tumor progression in all cell lines, albeit with variable efficacy compared to the clinical drug Pevonedistat, and again with the Daudi cells being the most responsive to the treatment. Transcriptomic and proteomic analyses indicated that RK-33-mediated inhibition of DDX3X, and DDX3X ablation through siRNA affects oxidative phosphorylation among other pathways and leads to an increase of intracellular reactive oxygen species (ROS). A CRISPR chemogenomic screen to identify synthetic lethalities linked to RK-33 implicated enzymes of the glutathione synthesis pathway and the Keap1-Nrf2-ARE pathway. We therefore tested the inhibition of the glutathione pathway with buthionine sulfoximine and showed that it reduced the CC50 of RK-33 in BL cells lines.ConclusionOur findings not only support DDX3X as a therapeutic target in BL but also provide evidence for a combinatorial treatment strategy to improve the efficacy of current treatments.